Biomimetic Clauson‐Kass and Paal‐Knorr Pyrrole Synthesis Using β‐Cyclodextrin‐SO3H under Aqueous and Neat Conditions ‐ Application to Formal Synthesis of Polygonatine†. Issue 34 (11th September 2018) - Patil, Rani N.; Kumar, A. Vijay
Abstract: The synthesis of pyrroles under mild conditions using sulfonic acid‐functionalized β ‐Cyclodextrin ( β ‐CD) as a supramolecular catalyst under aqueous conditions is demonstrated. Good to excellent conversion of various amines into pyrroles was observed without any side product formation. CD was found to play a dual role as a phase transfer reagent through inclusion as well as an acid catalyst thereby facilitating the smooth conversions of reactants. The advantages of this protocol are mild reaction conditions, sustainable catalyst and use of non‐toxic solvent water. Notably, the catalyst can be easily recovered and reused up to five cycles without any loss of catalytic activity. The developed protocol was successfully used as a key step for the formal synthesis of the alkaloid natural product Polygonatine. Abstract : Biomimetic synthesis of pyrroles is demonstrated using a supramolecular based sulfonic acid‐functionalized cyclodextrin as catalyst under aqueous and neat conditions, the developed protocol is use as a key step for the formal synthesis of natural product alkaloid Polygonatine.